Baylisascaris procyonis - Sadar, Miranda (Wildlife Rehabilitation Bulletin, 2021)
Baylisascaris procyonis or raccoon roundworm is present in over 90 percent of raccoons in some North American populations. While asymptomatic in raccoons, this parasite may affect other wildlife, domestic animals, and humans and has devastating health implications. This article provides information on B. procyonis and is intended to educate both wildlife rehabilitators and the public about potential risks associated with this disease.